Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2001
DOI: 10.1128/jvi.75.24.12058-12069.2001
|View full text |Cite
|
Sign up to set email alerts
|

The Major Human Immunodeficiency Virus Type 2 (HIV-2) Packaging Signal Is Present on All HIV-2 RNA Species: Cotranslational RNA Encapsidation and Limitation of Gag Protein Confer Specificity

Abstract: Deletion of a region of the human immunodeficiency virus type 2 (HIV-2) 5 leader RNA reduces genomic RNA encapsidation to about 5% that of wild-type virus with no defect in viral protein production but severely limits virus spread in Jurkat T cells, indicating that this region contains a major cis-acting encapsidation signal, or psi (⌿). Being upstream of the major splice donor, it is present on all viral transcripts. We have shown that HIV-2 selects its genomic RNA for encapsidation cotranslationally, renderi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
121
1

Year Published

2003
2003
2022
2022

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 81 publications
(125 citation statements)
references
References 51 publications
3
121
1
Order By: Relevance
“…Some groups have found packaging signals in positions analogous to those in HIV-1 (Garzino Demo et al, 1995;Sadaie et al, 1998). We have found consistently only a minor effect on packaging attributable to this region (McCann & Lever, 1997;Griffin et al, 2001;Kaye & Lever, 1999). Most groups agree that there is some contribution to packaging from regions upstream of the SD and we have, on repeated experiments, found this region to be the dominant packaging signal.…”
Section: Discussionmentioning
confidence: 92%
See 1 more Smart Citation
“…Some groups have found packaging signals in positions analogous to those in HIV-1 (Garzino Demo et al, 1995;Sadaie et al, 1998). We have found consistently only a minor effect on packaging attributable to this region (McCann & Lever, 1997;Griffin et al, 2001;Kaye & Lever, 1999). Most groups agree that there is some contribution to packaging from regions upstream of the SD and we have, on repeated experiments, found this region to be the dominant packaging signal.…”
Section: Discussionmentioning
confidence: 92%
“…For lentiviruses, regulatory and accessory proteins are encoded on multiply spliced mRNAs that are translated on free cytoplasmic ribosomes, where they could conceivably compete with the genomic RNA for packaging. For HIV-2, specificity is maintained by cotranslational packaging of the Gagencoding (Kaye & Lever, 1999;Griffin et al, 2001) (unspliced) message and apparent limiting availability of Gag available to capture other RNAs (Griffin et al, 2001). Given the genetic relatedness of the primate lentiviruses, it was of interest to see where the encapsidation signal of simian immunodeficiency virus (SIV) would be found.…”
Section: Introductionmentioning
confidence: 99%
“…Experiments from the Lever group showed that HIV-2 selects its genomic RNA for encapsidation cotranslationally (20). Two elements seem to mediate this activity: the nucleocapsid domain of the Gag protein and the 380-408 sequence located just upstream of the SL1 sequence in the leader RNA region, called the encapsidation signal or Ψ (Figure 8) (20). Mutagenesis studies have shown that retroviral encapsidation and dimerization elements overlap in vivo (for a review, see (40)).…”
Section: Discussionmentioning
confidence: 99%
“…The gag initiation codon is indicated by the solid horizontal bar below the sequence. ψ represents the core encapsidation signal of HIV-2 genomic RNA (nucleotides 380 to 408) defined by deletion mutagenesis (20). Thick lines indicate the PBS and the entire SL1 sequence (nucleotides 409 to 439; (29)).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation